Students’ Perceptions on the Implementation of Online Learning at a State High School in Yogyakarta - Irmalia, Virliana (Universitas Muhammadiyah Yogyakarta, 2022)
Introduction - Since Covid-19 has spread to Indonesia, the teaching and learning process is carried out online. During the implementation of online teaching and learning process, students faced challenges. The researcher also presents the research questions and objectives of the research. The benefits of the research for the teachers, the students, other researchers and the institution are provided in the section of significance of the study. Then, the researcher presents the organization of the chapters. Purpose - This research aimed to find out students’ challenges and strategies when doing online learning. Methodology - The researcher used a descriptive qualitative design. The researcher used interview as the data collection technique and interview guideline as the instrument of the research. Findings - There are eight challenges faced by the students, namely the unexplained materials, lack effective interaction between the students and the teacher, the inappropriate teacher’s time management, bad internet connection, the teachers’ unavailability to respond the students’ questions, incompetent teachers on online application, uncooperative and passive peer students, and difficulty in discussing in group work. Meanwhile, the strategies used by the students to overcome challenges when doing online learning included first by joining private course and looking for other sources, second by requesting additional time, third by prepared collaboration with friends, fourth by providing feedback and suggestions for the teachers, fifth by coordinating group members and being more active. Originality - In the application of online learning in the teaching and learning process, there are challenges that must be faced by students. The aims of this study is the researcher believe the students’ perceptions are very important in ensuring the quality of learning process, as the students are the most important subject who are affected by the implementation of online learning.